A method for reconstructing two-dimensional surface and internal temperature distributions in structures by ultrasonic measurements. (May 2020) - Wei, Dong; Yang, Xiaofeng; Shi, Youan; Xiao, Guangming; Du, Yanxia; Gui, Yewei
Abstract: A new method for simultaneously reconstructing surface and internal transient temperature distributions in structures is presented by ultrasonic measurements. The principle of ultrasonic thermometry is based on temperature dependence of the velocity of ultrasonic wave (acoustic velocity) propagating through heated structures. Considering the bending effect of ultrasonic propagation path in non-uniform temperature field, an approach for predicting two-dimensional ultrasonic propagation path is developed using the Fermat theory. Combining the advantages of the ultrasonic pulse-echo measurements and an inverse analysis of thermo-acoustic coupling problem, a reconstruction algorithm is proposed to estimate two-dimensional surface and internal temperature fields. The presented approach is discussed in some detail and a number of examples are given as verification to demonstrate the feasibility and reliability of this method. The surface and internal temperature profiles determined by ultrasound agree well with the exact values. In addition, the influences of bending effect of wave propagation, measurement error of ultrasonic wave propagation time, number and position of measurement points on the reconstruction of temperature fields are analyzed in detail. It shows that the presented method is a promising means for high-accurately and nondestructively determining surface and internal transient temperature distributions in heated structures. Highlights: The model is proposed by the inverse analysis of thermo-acoustic coupling problem. An approach is presented to consider the bending effect of wave propagation path. The new method has high precision, strong anti-noise ability and good applicability.